Different Views of Communication in Tourism: Understanding three Localities in Paraná/Brazil as Tourism Destination and Tourist Product - Nakatani, Marcia Shizue Massukado; Gomes, Ewerton Lemos; Nunes, Mylena Palazzo (Revista Turismo em Análise, 2017)
The communication of localities as places of tourism production and consumption derives primarily from different organizations and aims (official tourism organisms with promotional actions or private companies such as travel agencies and the efforts of advertising). This article discusses the differences between how localities are communicated applying the concepts of advertising and publicity. The research was based on documentary analysis of printed and digital promotional materials of the three main tourist destinations of the State of Paraná: Curitiba, Foz do Iguaçu and Paranaguá. Results shows that the locality is communicate with two distinct views and ways: as a tourism destination and as a tourist product. Thus, we conclude that for the same place it is possible to have different communication structures (only promotion or both promotion and commercialization aims), senders (who is speaking and its goals and interest) and message presentation (advertising or publicity).